THE EFFECT OF ENVIRONMENTAL FRIENDLINESS FANATICISM OF STUDENTS TOWARDS PURCHASE INTENTION AND PURCHASE DECISION OF ORGANIC FOOD - Kamilah, Khairiyah; Munandar, Jono Mintarto; Syamsun, Muhammad; Worapishet, Thirarut (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Organic food (OF) market is claimed as the fastest growing market in 20th century. Therefore, there are much research about finding factors that affect purchase intention towards OF, one of them is the Food Choice Questionnaire (FCQ), by which it is easy to assess nine distinct food choice motives and one important domain which is represented in FCQ is food choice based on ethical reasons. However, environmental protection or ecological motives is the most important motive to consume organic food. This study aims to see how fanaticism towards eco-friendly would affect the purchase intention and decision of organic food from the student’s perspective. This study uses 250 respondents from agricultural universities in Indonesia and Thailand, picked by purposive sampling method. This study found that fanaticism towards environmental friendliness affects purchase intention of organic food and purchase intention, simultaneously affects the purchase decision significantly in both countries. The moderating effect of price only affects the effect purchase intention on purchase decision of organic food in Indonesia. This happens because Thailand and Indonesia have different fanatic score and level of household monthly income. This study is helped by SmartPLS 3.0 to run the SEM-PLS and VALS Survey to analyze characteristics of respondents. Keywords: environment-friendly fanaticism, organic food, purchase intention, purchase decision, VALS Survey